2019
DOI: 10.1142/s1758825119500832
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polarized Shear Waves in FGPM Composite Structure with Imperfect Boundary: WKB Method

Abstract: Propagation behavior of horizontally polarized shear waves (SH-waves) in a piezo-composite structure is discussed, using the Wentzel–Kramers–Brillouin (WKB) method. The considered model is made by combining the Functionally Graded Piezoelectric Material (FGPM) layer and piezoelectric orthotropic substrate. The linear form spring model is considered to delineate the imperfection of interface. Moreover, the material properties of FGPM layer are varying linearly along the thickness direction. Dispersion relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, the general solutions of the ordinary differential equations (17) and (18) are assumed to bê…”
Section: The Full Analytical Solution Of Interfacial Shear Stress and Separation Conditions Of Claddings Excited By Love Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the general solutions of the ordinary differential equations (17) and (18) are assumed to bê…”
Section: The Full Analytical Solution Of Interfacial Shear Stress and Separation Conditions Of Claddings Excited By Love Wavesmentioning
confidence: 99%
“…The propagation theory of horizontal shear waves in cladding structures has always been one of the research hotspots of solid mechanics. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The displacement solution of a single cladding structure excited by horizontal shear waves was derived by the integral transformation method, and it was found that the displacement magnitude depends on the excitation magnitude. [26][27][28][29][30][31][32] The freely propagating solution of horizontal shear waves in the multilayer cladding structure was studied by the global matrix method and the transfer matrix method.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors revealed the impact of interfacial imperfections on the transmission of waves in PE structures [22][23][24]. Sahu et al [25] adopted the WKB method to demonstrate the impact of interfacial imperfection on phase velocity of shear wave in piezo-composite structure. Maity et al [26] explored the influences of imperfect bonding on velocity and attenuation of Love-type waves in a structure comprising viscoelastic medium and visco-micropolar medium.…”
Section: Introductionmentioning
confidence: 99%